ANALISIS PENGARUH COUNTRY OF ORIGIN DAN COLLECTIVISM TERHADAP PURCHASE INTENTION YANG DIMEDIASI OLEH CUSTOMER UNCERTAINTY - Syafira Khairani; Kurniawati Kurniawati (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
This study aims to find out how much influence Country of Origin and Collectivism have on purchase intention mediated by customer uncertainty by using a case study on local shoes in Indonesia. This study uses a descriptive quantitative research method. In sampling the technique used is a non-probability sampling technique with purposive sampling. For data collection in this study using the technique of distributing questionnaires and collecting secondary data. To calculate the results of the questionnaire distribution, a Likert scale with an interval scale was used. This research model is using path analysis. With data analysis using AMOS. The results showed that Country of Origin and Collectivism had a positive effect on Purchase Intention. Meanwhile, Country of Origin has a negative effect on Purchase Intention with Customer uncertainty as mediation and Collectivism has a negative effect on Purchase Intention with Customer Uncertainty as mediation.